Aku dan Alam (Beradik Kakak): Relasi Membatinkan Alam Sebagai Upaya Penguatan Resiliensi Spiritual Trauma Pasca Gempa di Tapanuli Utara - Tamba, Tiffany (Sekolah Tinggi Diakones HKBP, 2024)
This research aims to explore the strengthening of spiritual resilience in the face of post-earthquake trauma in the North Tapanuli region adopting Shelly Rambo’s trauma theology and Terence Fretheim’s relational theology. This research uses a relational-trauma theology approach with descriptive analysis techniques that will answer three important questions. First, what are the experiences of individuals or groups who experienced post-earthquake trauma in North Tapanuli in dealing with the event? Secondly, how do relationships of nurturing nature using the analogy of humans and nature ‘brothers and sisters jointly play a role in helping to awaken of individual or group spirituality in overcoming trauma? Thirdly, what are the challenges faced by individuals or groups in strengthening their spiritual resilience after the earthquake? This research shows that therapeutic entity can actively contribute to the treatment of trauma and that strengthening spiritual resilience through the mindfulness of nature relationships has great potential in helping individuals and groups deal with post-earthquake trauma.